Increasing robustness of in vitro assay for immnosuppressive effect of mesenchymal stromal/stem cells: The role of inflammatory cytokine production by peripheral blood mononuclear cells - Rumi Sawada; Shinji Kusakawa; Mika Kusuhara; Kazusa Tanaka; Takumi Miura; Satoshi Yasuda; Yoji Sato (Regenerative Therapy)
Introduction: The Quality by Design (QbD) approach for developing cell therapy products using mesenchymal stromal/stem cells (MSCs) is a promising method for designing manufacturing processes to improve the quality of MSC products. It is crucial to ensure the reproducibility and robustness of the test system for evaluating critical quality attributes (CQAs) in the QbD approach for manufacturing of pharmaceutical products. In this study, we explored the key factors involved in establishing a robust evaluation system for the immunosuppressive effect of MSCs, which can be an example of a CQA in developing and manufacturing therapeutic MSCs for treating graft-versus-host disease, etc, and we have identified method attributes to increase the robustness of a simple in vitro assay to assess the immunosuppressive effects of MSCs. Methods: We evaluated the performance of an assay system to examine the proliferation of peripheral blood mononuclear cells (PBMCs) activated with the mitogen phytohemagglutinin (PHA) when co-cultured with MSCs, the so-called one-way mixed lymphocyte reaction (MLR) assay. The MLR assay was performed on the same MSCs using 10 PBMC lots from different donors. In addition, 13 cytokine production levels in PHA-stimulated PBMCs were assessed. Results: The PHA-stimulated proliferation response of PBMCs, the action of MSCs in the MLR test, and the cytokine release of the respective PBMCs significantly differed among the PBMC lots (p < 0.05). A correlation analysis between the amounts of cytokines released by PBMCs and the immunosuppressive potency of MSCs showed that IFNγ, TNFα, CXCL10, PD-L1, HGF, and CCL5 production in PBMCs was significantly correlated with the MSC-mediated inhibition of PBMC proliferation (p < 0.05). Therefore, we selected two PBMC lots with high PBMC proliferation and PHA-stimulated cytokine (such as IFNγ and TNFα) release for the subsequent one-way MLR assay. The robustness of the established test system was confirmed by repeating the assay several times on different days for the same MSCs (coefficient of variation <0.2). Conclusions: To make robust the MSC immunosuppressive potency assay system, controlling the quality of PBMCs used for the assay is essential. Evaluating the inflammatory cytokine production capacity of PBMCs is effective in assessing the quality of the MLR assay system.